2022
DOI: 10.1007/s42452-021-04911-y
|View full text |Cite
|
Sign up to set email alerts
|

Bio- and phytoremediation: plants and microbes to the rescue of heavy metal polluted soils

Abstract: Bio- and phytoremediation, being encouraging terms implying the use of biological systems for cleansing purposes, have risen a worthy venture toward environmental restoration in discouraging scenarios, such as the augmentation of indestructible heavy metals. Hyperaccumulating plants and heavy metal resistant microbes own mechanisms embedded in their metabolism, proteins, and genes that confer them with “super characteristics” allowing them to assimilate heavy metals in order to amend polluted soils, and when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…In addition to the role of fungi in the removal of heavy metals, they also help in the removal of organic pollutants such as atrazine, 2,4-dichlorophenol, polychlorinated biphenyls (PCBs), 2,4,6-trinitrotoluene, and polycyclic aromatic hydrocarbons (PAHs), which can be removed by ectomycorrhizal fungi (ECM) [ 48 ]. Several microbes possess the remarkable ability to transform organic pollutants into less toxic compounds; these include Pseudomonas aeruginosa, Cupriavidus metallidurans , Pseudomonas putida , Aspergillus fumigatus , Aspergillus versicolor , Aspergillus tereus , Candida utilis , Penicillum chrysogenum , Saccharomyces cerevisiae , Rhodotorula mucilaginosa , and Phanerochaete chrysosporium [ 49 ].…”
Section: The Role Of Pgpms In Plant Detoxificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the role of fungi in the removal of heavy metals, they also help in the removal of organic pollutants such as atrazine, 2,4-dichlorophenol, polychlorinated biphenyls (PCBs), 2,4,6-trinitrotoluene, and polycyclic aromatic hydrocarbons (PAHs), which can be removed by ectomycorrhizal fungi (ECM) [ 48 ]. Several microbes possess the remarkable ability to transform organic pollutants into less toxic compounds; these include Pseudomonas aeruginosa, Cupriavidus metallidurans , Pseudomonas putida , Aspergillus fumigatus , Aspergillus versicolor , Aspergillus tereus , Candida utilis , Penicillum chrysogenum , Saccharomyces cerevisiae , Rhodotorula mucilaginosa , and Phanerochaete chrysosporium [ 49 ].…”
Section: The Role Of Pgpms In Plant Detoxificationmentioning
confidence: 99%
“…Phytohormones play a crucial role in modulating the morphology of roots. Several studies have reported that the microbes associated with plants have the capability to modulate the growth of roots [ 49 ]. ACC deaminase activity is a characteristic feature of both rhizospheric and endophytic bacteria, and is useful for plants experiencing abiotic stress conditions [ 66 ].…”
Section: The Role Of Pgpms In Abiotic Stress Tolerancementioning
confidence: 99%
“…To circumvent metal stress, bacterial endophytes have evolved multiple mechanisms, such as metal ions efflux outside of the cell, conversion of metal ions to less-toxic forms, precipitation, and biomethylation of metal ions [ 28 , 121 ]. Recent studies have highlighted that inoculation of plant seeds/soil with bacterial endophyte (metal resistant) promoted plant growth and enhanced phytoremediation in metal-contaminated soil via improved nutrient uptake, cell elongation, phytostabilization, and metal stress alleviation [ 122 , 123 , 124 ]. In the present time, fungal endophytes are also emerging as prospective candidates in HM tolerance and mitigation.…”
Section: Harnessing Plant Endophytic Microbiome For Heavy Metal Toler...mentioning
confidence: 99%
“…However, these techniques are facing some problems, such as the high consumption of solvents and other chemicals, the low selectivity and purity of the extracted elements and low efficiency of metals recovery from very diluted wastewater [ 5 , 6 ]. Furthermore, the risks of secondary environment pollution and possible negative impact on workers’ health have reduced the attractiveness of mentioned processes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even microorganisms of different taxonomic groups are successfully applied to degrade metal ions into less toxic forms or eliminate them from the environment [ 7 , 8 , 10 , 15 , 16 ]; however, in the literature there is no information about their application for Er(III) recovery.…”
Section: Introductionmentioning
confidence: 99%